HIGH FUNCTIONING AUTISTIC STUDENTS’ LEARNING STRATEGIES IN WRITING TEXTS IN INCLUSIVE SCHOOLS - Muhammad Soali; Benny Krisbiantoro (J-LEE - Journal of Law, English, and Economics, 2021)
The aims of this study were to: 1) describe the process of how HFA students learn descriptive texts in inclusive classes, 2) disclose the influencing factors of HFA students’ success in writing descriptive texts in inclusive classes, 3) examine the learning strategies used by the HFA students in writing descriptive texts in inclusive classes. A qualitative study was used as a method of this study. The participants of this study were four HFA students at the seventh grade of inclusive schools. This study was conducted in two schools in Junior High School of Yogyakarta and Purwokerto, Central Java. Interview, observation, and documentation were used to collect the data. Moreover, this study used data condensation, data display, conclusion drawing, or verification to analyze the data. The results generally showed that the pictures were employed by HFA students as inspiration to enhance their ability in writing descriptive texts. Involving them into fun activities could enhance social skill dealing with their social impairments. HFA students choose particular strategies to accomplish particular task. There are some crucial factors that determine the success of autistic students in writing English descriptive texts. They are internal factors and external factors. Internal factors cover: motivation 1) autistic students’ perception on learning strategies used, 3) learning experiences. Internal factors consist of: 1) environment; 2) teacher’s strategies; 4) role of special guidance teachers. In addition, two dominant strategies are used when learning English. They are memory strategies and cognitive strategies. The last, one of the factors that influence the students’ choice of learning strategies is teacher’s teaching strategies. Keywords: Learning Strategies, English Learning Strategies, Memory strategies, Cognitive Strategies, Autistic Students, HFA Students.